Subacute forms of heterotopic peritoneal echinococcosis: hydatic pseudoascites and cystic peritoneal hematocele with intact hydatid - Praderi, Raúl; López, Elena; Rago, Marta (Cirugía del Uruguay, 2021)
The paper refers to two cases of heterotopical peritoneal primitive echinococcoús which are rather rare. In one case, the parturition to the peritoneum of a very large hydatid of hepatic origin, simulated an ascitis. The other refers to the rupture of a splenic hydatid cyst which caused a serious peritoneal hemorraghe and the parturition of the intact hydatid. The hemorraghe was encysted in the left subphrenic region with the membrane intact in the interior of the hematocele.